ANALISIS SEMANTIK: POLISEMI VERBA QᾹMA DALAM AL-QUR’AN - rohman, Taufikur (Departemen Pendidikan Bahasa Arab, 2018)
This study examines the diversity of meanings of the Qama verbs contained in the verses of the Qur'an. This study aims to find out the basic meaning and the extended meaning of the Qama verb. This research uses a qualitative approach with descriptive methods. The object of this research is the verb Qama. Data sources used were Al-Qur'an Manuscripts translated 30 juz, commentaries, and the internet. The data collection technique used is the note taking technique. In this study, the writer collected data from the main source, namely the Al-Qur'an Manuscripts, then the writer recorded the data in the form of sentences containing the meaning of the Qama verb. Data that has been collected, then classified. The results showed that the Qama verbs contained in the Qur'an have 10 different meanings, consisting of 1 basic meaning and 9 extended meanings. The basic meaning of the QÄma verb is to stand, while the meaning of the expansion of the QÄma verb is to carry out, take care of, replace, hold, occur, appear, face, stop, and wake up.